2012
DOI: 10.1088/0022-3727/45/25/255202
|View full text |Cite
|
Sign up to set email alerts
|

Plasma decay in air and O2 after a high-voltage nanosecond discharge

Abstract: This paper presents the results of experimental and theoretical studies of an afterglow in room temperature air and O2 excited by a high-voltage nanosecond discharge for pressures between 1 and 10 Torr. We measured time-resolved electron density by a microwave interferometer for initial electron densities in the range (2–3) × 1012 cm−3. Discharge uniformity was investigated by optical methods. The balance equations for charged particles and electron temperature were numerically solved to describe the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The fulfillment of this condition greatly simplifies the theoretical analysis of experimental data. It is these conditions that were realized, e.g., in experiments [96,97], where the dynamics of changes in the electron density during plasma decay in air (1-10 Torr) after a highvoltage nanosecond discharge with a specific energy deposition of 0.002-0.02 eV/mol was studied using microwave interferometry. Numerical simulation [96,97] showed that plasma decay under these conditions can be described on the basis of a fairly simple kinetic scheme, in which the main channel for the loss of charged particles is electron-ion recombination with positive ions, including cluster ions formed in the discharge afterglow.…”
Section: Decay Of Non-equilibriummentioning
confidence: 99%
See 4 more Smart Citations
“…The fulfillment of this condition greatly simplifies the theoretical analysis of experimental data. It is these conditions that were realized, e.g., in experiments [96,97], where the dynamics of changes in the electron density during plasma decay in air (1-10 Torr) after a highvoltage nanosecond discharge with a specific energy deposition of 0.002-0.02 eV/mol was studied using microwave interferometry. Numerical simulation [96,97] showed that plasma decay under these conditions can be described on the basis of a fairly simple kinetic scheme, in which the main channel for the loss of charged particles is electron-ion recombination with positive ions, including cluster ions formed in the discharge afterglow.…”
Section: Decay Of Non-equilibriummentioning
confidence: 99%
“…This process has been well studied for atomic ions [114,115] and has hardly been studied for molecular ions. At the same time, it was suggested that the rate of three-body recombination for molecular ions (in particular, for ions [96,97,116]) can be much higher than for atomic ions and that, in these cases, there are different dependences of the recombination rate coefficients on Т е .…”
Section: Decay Of Non-equilibriummentioning
confidence: 99%
See 3 more Smart Citations